SPECIFIC PROBLEMS OF SOCIO-ORIENTED INNOVATIVE COMPANIES - Olga Alexandrovna Boris (Вестник Северо-Кавказского федерального университета, 2022)
The article describes the problems of socially oriented and innovative enterprises are the main ways to solve them.